Translation as a Communication Strategy in Representing National Culture - Akkaliyeva, Aizhan (Social Inclusion, 2021)
The linguistic trinity policy, which has been implemented in Kazakhstan since its independence in the 1990s, is aimed at integrating translation into global processes. Kazakh-Russian bilingualism, caused by the historical and geopolitical proximity of the two countries, is now turning into trilingualism, joining up with English as the dominant language for international communication. Literary translation as a part of cross-cultural communication is also involved in social inclusion processes, contributing to the exchange of cultural values and a better understanding of modern multilingual Kazakhstani society. This article focuses on the issue of presenting Kazakh literature in translation through a mediating language and the research involves an analysis of culture-related lexemes as representations of a nomadic lifestyle in the mirror of intercultural communication. The authors highlight cultural and linguistic aspects of Kazakh transmitted from the mediatory Russian into the target English. Based on a review of previous findings on indirect literary translation, this article discusses whether a mediating language affects the inclusion of Kazakh culture in the globalization process.